Assessing Mechanical Difference in Fulcrums for Balanced Cable Bone Segment Transport - Rhys Leigh Richmond; Stephanie V. Kaszuba; Steven M. Tommasini; David B. Frumberg (Journal of Limb Lengthening & Reconstruction)
Background: Multiple options exist for fulcrums in balanced cable bone segment transport (BC-BST) procedures, but there is no consensus among orthopedic surgeons on best practices. Aims and Objectives: This study investigates the mechanical differences between a variety of fulcrums used to perform this reconstructive technique. Materials and Methods: A custom testing rig was built to determine the tension-modifying effects of different fulcrums on the BC-BST system. Results: The stiffness of the system was inversely related to the displacement of the spring, and the least stiff system occurred in fulcrums without threads and of larger diameter. Conclusion: These observed differences suggest that the diameter and type of fulcrum used impact the BC-BST system and there may be an opportunity for greater personalization of the pull tension.